DEVELOPMENT OF VERTICAL AXIS MARINE CURRENT TURBINE FOR SUNDA STRAIT APPLICATION - Suprayogi, Dedy Triawan; Sudrajad, Agung; Pinem, Mekro Permana; Yusuf, Yusvardi; Haryadi, Haryadi; Susilo, Sidiq (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2023)
The development of Renewable Energy (RE) has become one of the priorities that has been promoted by various governments around the world, as a step towards implementing green energy in accordance with the Paris Agreement. The sea as one of the largest parts of the territory in Indonesia must be managed for its energy because it has quite large energy potential. One of them is ocean currents. The Sunda Strait is a very strategic strait and has ocean currents that have the potential to develop energy to be used as a source of electrical energy. Therefore the development of a suitable turbine design is urgently needed in this strait area. In previous research the simulation and experimental work have confirmed that the Savonius rotor can be worked in the low speed marine current. This is will be relevant with Sunda Strait condition that have current 0.4 – 1 m/s. The experiment also shows that the rotor provided torque 0.36 Nm with 11.97 RPM therefore can generated 0.45 Watt